An Integration between Baluch’s Costumes and Contemporary Iranian Woman: An Apparel on Aesthetics Elements - Alipour, Nafiseh; Naeini, Hassan Sadeghi; Rahmani, Sara (Journal of History Culture and Art Research, 2017)
This paper investigates costume fashion design of a specific Iranian group, specifically Baluch people. In this study, we have conducted a research to make an appropriated and functional association between modern daily fashion and Iranian local regional clothes as a social and cultural identity characteristic. There are some textile manufacturing industries in Iran, in which about 400,000 employees are working in different branches of production. Baluch’s history indicates that their traditional costume has been derived from Iranian fundamental designs. Baluch culture has long been settled in the East of Iran. Baluch people are among the few Iranian tribes who are committed to their local costumes. This study is a cross-sectional survey in which 100 volunteers filled out the 7-scale questionnaires throughout some social networks among Iranian adult women (Age: 30±0.5). We also gathered some information based on the literature review, observation and museums and exhibitions of handicrafts visits. In this study, we focused on Baluch ethnic costumes, and we studied some articles in this field to develop a practical method in observing and assessing the sample costumers. Our data analysis indicates that 32% of volunteers partially agree that they have tendencies to pick fashionable clothing, 34% of volunteers agree that they prefer to be unique, 33% of volunteers partially agree that the national identity is important when it comes to fashion, and 28% of them partially agree about the importance of local origin of fashion. These results also express that 36% of volunteers partially agree that the traditional Iranian costume is appealing to them, and 33% of them partially agree that traditional costumes are usable as contemporary clothing. Per foregoing features of Baluch costumes in aesthetic, social and cultural context, and obtained results and relevant statistical analysis, it seems that Baluch costumes aesthetical identity can be applied in contemporary Iranian women’s clothing, considering fashion principles. Last but not least, design process is based on questionnaire results and the traditional Baluch costume analysis. Our findings show that the importance of considering some criteria during design process, such as national identity, tendency to wear local and colorful costumes, applying traditional handcrafts and motifs on contemporary clothing, uniqueness and elegance. The presented design is recommended based on the deduced results of previous phases.